The Introduction of Academy Schools to England's Education - Andrew Eyles; Stephen Machin (Institute for the Study of Labor (IZA), 2015)
We study the origins of what has become one of the most radical and encompassing programmes of school reform seen in the recent past amongst advanced countries the introduction of academy schools to English secondary education. Academies are state schools that are allowed to run in an autonomous manner which is free from local authority control. Almost all academies are conversions from already existent state schools and so are school takeovers that enable more autonomy. Our analysis shows that this first round of academy conversions that took place in the 2000s generated significant improvements in the quality of pupil intake and in pupil performance. There is evidence of heterogeneity as improvements only occur for schools experiencing the largest increase in their school autonomy relative to their predecessor state. Analysis of mechanisms points to changes in headteachers and management structure as key factors underpinning these improvements in pupil outcomes.
Keywords: I20; I21; I28; 330; academies; pupil intake; pupil performance